RESTORE-IMI 1: A Multicenter, Randomized, Double-blind Trial Comparing Efficacy and Safety of Imipenem/Relebactam vs Colistin Plus Imipenem in Patients With Imipenem-nonsusceptible Bacterial Infections. (10th August 2019) - Motsch, Johann; Murta de Oliveira, Cláudia; Stus, Viktor; Köksal, Iftihar; Lyulko, Olexiy; Boucher, Helen W; Kaye, Keith S; File, Thomas M; Brown, Michelle L; Khan, Ireen; Du, Jiejun; Joeng, Hee-Koung; et al.
Abstract: Background: The β-lactamase inhibitor relebactam can restore imipenem activity against imipenem-nonsusceptible gram-negative pathogens. We evaluated imipenem/relebactam for treating imipenem-nonsusceptible infections. Methods: Randomized, controlled, double-blind, phase 3 trial. Hospitalized patients with hospital-acquired/ventilator-associated pneumonia, complicated intraabdominal infection, or complicated urinary tract infection caused by imipenem-nonsusceptible (but colistin- and imipenem/relebactam-susceptible) pathogens were randomized 2:1 to 5–21 days imipenem/relebactam or colistin+imipenem. Primary endpoint: favorable overall response (defined by relevant endpoints for each infection type) in the modified microbiologic intent-to-treat (mMITT) population (qualifying baseline pathogen and ≥1 dose study treatment). Secondary endpoints: clinical response, all-cause mortality, and treatment-emergent nephrotoxicity. Safety analyses included patients with ≥1 dose study treatment. Results: Thirty-one patients received imipenem/relebactam and 16 colistin+imipenem. Among mITT patients (n = 21 imipenem/relebactam, n = 10 colistin+imipenem), 29% had Acute Physiology and Chronic Health Evaluation II scores >15, 23% had creatinine clearance <60 mL/min, and 35% were aged ≥65 years. Qualifying baseline pathogens: Pseudomonas aeruginosa (77%), Klebsiella spp. (16%), other Enterobacteriaceae (6%). Favorable overall response was observed in 71% imipenem/relebactam and 70% colistin+imipenem patients (90% confidence interval [CI] for difference, –27.5, 21.4), day 28 favorable clinical response in 71% and 40% (90% CI, 1.3, 51.5), and 28-day mortality in 10% and 30% (90% CI, –46.4, 6.7), respectively. Serious adverse events (AEs) occurred in 10% of imipenem/relebactam and 31% of colistin+imipenem patients, drug-related AEs in 16% and 31% (no drug-related deaths), and treatment-emergent nephrotoxicity in 10% and 56% ( P = .002), respectively. Conclusions: Imipenem/relebactam is an efficacious and well-tolerated treatment option for carbapenem-nonsusceptible infections. Clinical Trials Registration: NCT02452047. Abstract : Imipenem/relebactam (IMI/REL) is a suitable treatment option for serious gram-negative infections, including those caused by carbapenem-nonsusceptible pathogens in high-risk patients. IMI/REL may be preferable to colistin-based therapy, given comparable efficacy but IMI/REL's significantly lower nephrotoxicity and improved overall tolerability.